El poder de la técnica como (¿la?) técnica del poder: Procesos políticos y análisis de redes sociales en el marco de la gubernamentalidad algorítmica. - Ruffini, María Luz (Universidad Nacional de Villa María, 2021)
At present, it is necessary to incorporate into the analysis of politics and power the reflection about technique and life’s digitization processes -particularly of the structures, codes and behaviors in social networks- for which it is essential to retake epistemological positions, theoretical tools and methodological practices from various fields of knowledge. In this framework, we will work the ontological problem of the place of technology and, in particular, the role of digital technologies and algorithms in the process of global social order constitution. Then, we will delve into the question of power through the foucaultian notion of “governmentality” and the reappropriation of it by Rouvroy and Berns through the notion of “algorithmic governmentality”. Finally, and based on the above, we will show the main lines of a methodological design that was explored during 2019, which can provide clues for the future development of analytical tools to address political processes from a broad perspective and according to the profound transformations contemporaries of life in common.